Bilingual Training and Cultural Narrative Development for the Creative Economy of Balkondes Ngargogondo - Muhammad Nur Hanif; Boris Ramadhika; Atika Kurnia Putri; Arviani Eva Nur Rahmawati; Pujiyati (PT Inovasi Pratama Internasional, 2026)
This community service program aims to improve the basic skills of village-owned enterprise (BUMDes) homestay managers in the Borobudur area in writing and producing digital content as a community-based tourism branding strategy. The program will be held over four months (September–December 2025) and will involve 15 participants. The implementation method includes four training sessions and ten activities: bilingual training, local cultural history narrative training, content creation training, and videography and photography training. The ten activities are: Human Resource Observation and Mapping, Bilingual Public Service Simulation, Field Observation of Local Cultural and Historical Sites, Compiling Local Cultural History Narratives, Producing Promotional and Cultural Content, Publication and Social Media Management, Field Photo Shoots, Field Documentation, Short Profile Video Production, and Work Exhibitions and Presentations. The results of the community service program indicate that the integration of bilingual training, cultural narrative training, content creation, and videography and photography training effectively increased participants' knowledge, technical skills, confidence, and cultural awareness within the context of service delivery and tourism village promotion. Such training can also be used as an effective and sustainable strategy to increase the competitiveness of community-based creative economies in tourism villages.